Pentingnya Publikasi Kegiatan Di Era Media Sosial - Nurliya Apriyana; Lingga Yuliana (Universitas Katolik Widya Karya Malang, 2023)
The ongoing technological advancements have significantly impacted people across all strata of society. The ease of obtaining information nowadays has become a hallmark of technology. This underscores the importance of utilizing technology appropriately as a platform to publicize the activities of empowerment within their work scope. This webinar aims to emphasize the significance of conducting publicity through social media by the administrators and members of the Family Empowerment and Welfare Movement (PKK), so that the activities and performance of the PKK empowerment team can be known to the general public, especially social media users. This way, the forms of activities can serve as a track record and be accountable to the community. Through social media, the dissemination of activity publications can occur swiftly and accurately, acting as a two-way communication tool to interact with the public. The content conveyed through social media reflects the identity of the social media owner, and social media has the capability to present mass justifications. Lastly, social media serves as a convenient and rapid, effective, and economical tool for communicating messages.